“The View Ascertains the Death”: Laypeople, the Senses, and Determining a Cause of Death in Eighteenth-Century London - Jahudka, Ines (Renaissance and Reformation / Renaissance et Réforme, 2025)
This article explores the significant role laypeople played in the early modern post-mortem process in eighteenth-century England, focusing on their sensory engagement with the deceased. Using knowledge drawn from personal experience, family lore, and self-help manuals on home “physick,” laypeople used their sensory understanding of bodies in sickness and health to help determine a cause of death. By investigating how sensory knowledge shaped the interpretation of death, this article explores how laypeople’s tactile and visual interactions with the body influenced the judicial process. This study underscores how lay knowledge informed the legal system’s inquiries into death, and how lay sensory experience and expertise played pivotal roles in early modern judicial conclusions.